Scrutinizing the potential use of Discord application as a digital platform amidst emergency remote learning - Endang Wahyuningsih; Baidi Baidi (Journal of Educational Management and Instruction (JEMIN), 2021)
A common challenge encountered by educators to engage in an emergency remote learning is the selection of an effective digital platform to assist teaching and learning activities. Drawing on this issue, this study offers a practical solution by scrutinizing the potential use of android-based application named Discord as a digital platform to conduct online teaching and learning. To this end, a group of elementary school teachers and students enrolled in Islamic religious and moral education courses was involved as participants in a descriptive qualitative research by employing interview, observation, and documentation as instruments to collect the required data. The results demonstrated that Discord android-based application was proven to be an alternative for elementary school educators as a digital learning platform during the emergency remote learning in the age of Covid-19 pandemic. The results of observation further showed that online teaching-learning activities using Discord application could successfully create communicative digital learning environment which was interesting and enjoyable for the students. Despite the potential advantages, a number of challenges were also discussed in this study. The results of this study contribute as a practical insight for teachers and students in assisting online learning activities as Discord application helps them experience a new nuance of distance learning.